Increasing Christian Education Learning Motivation Through a Scientific Approach - Lena Simanungkalit; Taripar Aripin Samosir; Senida Harefa (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study is to determine the positive and significant differences in Christian Education learning motivation in students using a scientific approach with Christian Education learning motivation in students using a conventional approach in class XI majoring in Culinary Engineering of SMK Negeri 1 Siatas Barita Learning Year 2023/2024. This research method is a quantitative approach with quasi-experimental methods and with post-test only control group design. The population is all students who are Christians class XI of the Department of Culinary Engineering of SMK Negeri 1 Siatas Barita for the 2023/2024 Learning Year which amounts to 63 people. The research sample was determined by Saturated Sampling, namely class XI Culinary 1 students totaling 32 people as an experimental class using a scientific approach and class XI Culinary 2 totaling 31 people as a control class using a conventional approach. The instrument used in this study was a questionnaire item of 32 items. The research data for the questionnaire were analyzed using the Separated Variance t-test formula. From the calculation results, tcount = 5.0448 > ttable (α/2=0.05/2=0.025) = 1.999. It turns out -tcount < -ttable (-5.0448 < -1.9996). The calculated value is in the area of the rejection curve H0 and acceptance Ha. Thus, it can be concluded that the research hypothesis is accepted, namely that there are positive and significant differences in the motivation to learn Christian Education in students using a scientific approach with the motivation to learn Christian Education in students using a conventional approach in class XI majoring in Culinary Planning, SMK Negeri 1 Siatas Barita Learning Year 2023/2024. The difference in motivation to learn Christian Education in grade XI students of the Department of Culinary Engineering of SMK Negeri 1 Siatas Barita, North Tapanuli Regency for the 2023/2024 Learning Year is known from the average motivation to learn Christian Education in students with a scientific approach is 89.9063, higher than the average motivation to learn Christian Education in students with a conventional approach, which is 82.6452.